PROGRAM STUDENT OF THE MONTH SEBAGAI PROSES HABITUASI NILAI DISIPLIN SISWA - Fazriah, Fani Nurul; Lindawati, Yustika Irfani (Universitas Tanjungpura, 2022)
Student of the month is a program dedicated to giving appreciation and awards from the school to the best students with specific criteria. The selection of student of the month is based on the following criteria: (1) The percentage of student attendance in that month is above 90%, (2) Good character, (3) Obeys madrasa regulations, (4) Active in teaching and learning activities and extracurricular activities. This study aims to identify the process of implementing the student of the month program, determine the implementation of the student of the month program at MAN 2 Serang, and assess the impact of the student of the month program on students at MAN 2 Serang. This research is included in the descriptive analysis. This research is qualitative. The collection technique was done through interviews, documentation, and observation. Research subjects in this study were determined purposively, namely the selection of research subjects intentionally by researchers based on specific goals and criteria. The determination of research subjects is based on particular characteristics or characteristics that assess the researcher's subjectivity. The data analysis technique used is the inductive analysis technique. The study results concluded that the student of the month program led to a change in student habits, where there was a change in student behavior patterns, especially in increasing discipline. The sustainability of the program, which is carried out every month, has implications for forming a habitus for students.